2010
DOI: 10.1017/s0950268810001810
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus genotypes co-circulating in Europe between 2006 and 2009 as determined by EuroRotaNet, a pan-European collaborative strain surveillance network

Abstract: SUMMARYEuroRotaNet, a laboratory network, was established in order to determine the diversity of co-circulating rotavirus strains in Europe over three or more rotavirus seasons from 2006/2007 and currently includes 16 countries. This report highlights the tremendous diversity of rotavirus strains co-circulating in the European population during three years of surveillance since 2006/ 2007 and points to the possible origins of these strains including genetic reassortment and interspecies transmission. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
255
7
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(293 citation statements)
references
References 33 publications
(59 reference statements)
25
255
7
6
Order By: Relevance
“…Genotyping is considered to be a valid proxy for serotyping, and is adopted universally. As a result, a large amount of data is being accumulated concerning rotavirus genotypes and serotypes circulating worldwide [10,11], which is valuable to confirm the adequacy of current vaccines in relation to emergence and evolution of viral strains [12,13]. Currently, at least 27 different G-types and 35 P-types are recognized among human or animal worldwide [14], and increasing evidence of zoonotic transmission of animal rotaviruses to humans, involving reassortment mechanisms during dual infection, has strengthened the threat of novel rotavirus strains emergence from domestic and wild animals with respect to vaccine efficacy [15].…”
Section: Serotypes Genotypes and Immunitymentioning
confidence: 99%
“…Genotyping is considered to be a valid proxy for serotyping, and is adopted universally. As a result, a large amount of data is being accumulated concerning rotavirus genotypes and serotypes circulating worldwide [10,11], which is valuable to confirm the adequacy of current vaccines in relation to emergence and evolution of viral strains [12,13]. Currently, at least 27 different G-types and 35 P-types are recognized among human or animal worldwide [14], and increasing evidence of zoonotic transmission of animal rotaviruses to humans, involving reassortment mechanisms during dual infection, has strengthened the threat of novel rotavirus strains emergence from domestic and wild animals with respect to vaccine efficacy [15].…”
Section: Serotypes Genotypes and Immunitymentioning
confidence: 99%
“…43 In addition, extensive global epidemiological surveys have confirmed that G1-G4 as well as P [8] and P [4] genotypic strains are of global epidemiologic importance. 43,44 It is of note that uncommon G and P types causing a high incidence of human infection have been reported in various regions worldwide including G8, G9, G10, G12, and P [6]. [45][46][47][48][49] Since in nature, almost all human rotavirus G types have been detected in combination with P [8], P [4] or P [6] specificity, the P2-P[8]DVP8*-P [8]DVP8* and P2-P[8]DVP8*-P[6]DVP8* vaccines generated in this study could be used at a minimum singly or preferably in bivalent formulation to provide antigenic coverage against almost all the rotavirus G (VP7) types and the 2 major P types of global as well as regional epidemiologic importance, including new and emerging G8, G9 and G12 rotaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the uncommon RVA reported worldwide, particular attention is given to animal-derived genotypes that may become able to infect the human host, such as RVA strains displaying G6, G9 and G10 genotypes (Libonati et al, 2014;Luchs & Timenetsky, 2014;Matsushima et al, 2012;Mijatovic-Rustempasic et al, 2014;Mukherjee et al, 2012). Some of these are candidates to become major human genotypes, as was previously observed for the G9 genotype (Gentsch et al, 2009;Iturriza-Gó mara et al, 2011;Matthijnssens et al, 2010;Santos & Hoshino, 2005), and might represent a challenge for the efficacy of current anti-rotavirus vaccines, posing a need for RVA strain surveillance programmes (Banerjee et al, 2006;Iturriza-Gó mara et al, 2011).…”
Section: Introductionmentioning
confidence: 93%